2005
DOI: 10.1074/mcp.m400128-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Analysis of Lysosomal Integral Membrane Proteins Reveals the Diverse Composition of the Organelle

Abstract: Lysosomes are endocytic subcellular compartments that contribute to the degradation and recycling of cellular material. Using highly purified rat liver tritosomes (Triton WR1339-filled lysosomes) and an ion exchange chromatography/LC-tandem MS-based protein/peptide separation and identification procedure, we characterized the major integral membrane protein complement of this organelle. While many of the 215 proteins we identified have been previously associated with lysosomes and endosomes, others have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 59 publications
6
134
0
4
Order By: Relevance
“…In contrast, LOPIT analyses the steady-state partitioning of proteins to establish their primary site of residency. A number of proteins previously reported as lysosomal (31,32) were identified in our analysis but did not cluster with the established lysosomal markers, indicating that they were not unique to the lysosome or predominantly localized there in DT40. Examples include nicastrin, a component of the gamma-secretase complex, which is located close to our PM cluster on PCA plots, and NiemannPick C1, found in an intermediate location close to the lysosome and Golgi clusters.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, LOPIT analyses the steady-state partitioning of proteins to establish their primary site of residency. A number of proteins previously reported as lysosomal (31,32) were identified in our analysis but did not cluster with the established lysosomal markers, indicating that they were not unique to the lysosome or predominantly localized there in DT40. Examples include nicastrin, a component of the gamma-secretase complex, which is located close to our PM cluster on PCA plots, and NiemannPick C1, found in an intermediate location close to the lysosome and Golgi clusters.…”
Section: Resultsmentioning
confidence: 72%
“…Rather than this being a problem with protein detection, we suggest that this reflects the steady-state protein distribution within the cell, and that there are actually relatively few membrane proteins uniquely localized to the lysosome. Although other proteomic studies focusing on lysosome membranes have reported a wide range of constituents (31,32), these have been based on the analysis of enriched lysosomal preparations and represent catalogues of all the proteins associated with the organelle. Included are residents of multiple compartments or proteins only transiently associated with the lysosome.…”
Section: Resultsmentioning
confidence: 99%
“…Several mammalian ABC transporters localize to late endosomes/lysosomes, including the ABCB transporter (MDR/TAP) member 6, ABCA1, ABCA2, ABCA3, ABCA5, ABCB9 and the ABCC transporter MRP2 (Bagshaw et al, 2005;Chen et al, 2005;Cheong et al, 2006;Kubo et al, 2005;Neufeld et al, 2004;Zhang et al, 2000;Zhou et al, 2001). ABCA1 traffics between late endosomes and the cell surface and is required for the efflux from the cell of cholesterol in late endosomes (Chen et al, 2005;Neufeld et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Acid phosphatases catalyze the hydrolysis of orthophosphate monoesters from a wide variety of substrates, including phosphorylated proteins, under acid conditions. 26,27 Several acid phosphatase (ACP) genes are known in mammals, of which ACP2 encodes the main lysosomal acid phosphatase.…”
Section: Cell Morphology and Cell Deathmentioning
confidence: 99%